Understanding parental role in children’s participation in decision-making during hospitalization: an ethnographic study in Malaysia - Lee, Siew Pien (2023)
Background: Despite a growing recognition internationally that children have a right to participate in matters that affect their lives, they are not always involved in decision-making processes concerning their health care. There is a deficit information on how parents influence children’s participation in decision-making in health care. The aim was to explore the role parents assume in the interaction process surrounding children’s participation in communication exchanges and decision-making in a paediatric oncology unit in Malaysia. Materials and Methods: This study adopted a focused ethnography design within a constructivist research paradigm. Participant observations and semi structured interviews were conducted with 22 parents, 22 children, and 19 nurses at a paediatric oncology unit in Malaysia. All observation fieldnotes and interview recordings were transcribed verbatim. Focused ethnographic data analysis technique was performed to analyze the data. Results: Three themes emerged from the situations where parents played their roles in the communication and decision-making process involving their child: (i) facilitators of communication, (ii) communication brokers, and (iii) communication buffers. Conclusion: Parents controlled the process of decision-making concerning their children’s health care, while the children prefer and welcoming parents as their consultant in decision-making process with regards to their health care.